Chemical composition and leishmanicidal activity of Pulicaria gnaphalodes essential oil - G. Asghari; F. Zahabi; A. Eskandarian; H. Yousefi; M. Asghari (Iranian Society of Pharmacognosy, 2014)
Background and objectives: Several natural compounds have been identified for the treatment ofleishmaniasis. Due to a few safe drugs and the side effects caused by available chemotherapy, some new drugs for treatment of leishmaniasis are requested.  The genus Pulicaria (Asteraceae) is represented in the flora of Iran by five species. Phytochemical studies on Pulicaria species have revealed some flavonoids and terpenoids with leishmanicidal activity. In the present investigation chemical composition and leishmanicidal activity of Pulicaria gnaphalodes essential oil have been studied. Methods: The essential oil of the aerial parts of the plant was obtained by Clevenger apparatus and was analyzed by GC/MS. Antileishmanil activity was assessed against promastigoes of Leishmania major. Results:The major components from P. gnaphalodes essential oil have been reported to be geraniol, 1,8-cineole, chrysanthenone, α-pinene, chrystanthenone, α-terpineol and filifolone. The alcohol monoterpenes with contribution of 25.04% constituted the major portion of the essential oil, while hydrocarbon monoterpenes and hydrocarbon sesquiterpenes with contribution of 7.08% and 2.38%, respectively occupied the next rates.In the present experiment the essential oil of P. gnaphalodes progressively inhibited Leishmania major growth in concentrations ranging from 0.125 to 50 µL/mL (parasite culture) in 24 h. The essential oil at 50 µL/mL eliminated the promastigotes at the beginning of treatment. It showed antileishmanial activity in concentration of 1.06 µL/mL and destroyed all parasits in 24 h.  Conclusion: Pulicaria gnaphalodes antileishmanial activity, could suggest the species and constituents as possible lead structures for antileishmanial drug discovery.